Social media addiction (SMA), internet gaming disorder (IGD), and online shopping addiction (OSA) as predictors of psychological well-being (PWB) - Ng, Jing Rou; Sim, Jing Xuan Vadelyn; Goh, Vivian Zhi Xuan (2024)
The widespread use of the Internet in Malaysia, especially among young adults, has led to concerns about Internet addiction's impact on psychological well-being (PWB). High rates of social media engagement, online shopping, and gaming have been linked to poor PWB. This study aims to investigate how social media addiction (SMA), Internet gaming disorder (IGD), and online shopping addiction (OSA) predict PWB among young adults in Malaysia, addressing gaps in understanding and contributing to interventions for this demographic. Utilizing a quantitative approach, an online survey gathered data from 107 participants, aged 18 to 26, engaging in social media, online gaming, and shopping for at least one year. The study hypothesized that SMA, IGD, and OSA negatively predict PWB. Contrary to expectations, SMA and OSA were not significant predictors of PWB, indicating a more nuanced relationship than previously assumed. Interestingly, while SMA showed a non-significant positive relationship, IGD negatively predicted PWB, aligning with existing literature on the adverse effects of excessive gaming. This study used the Uses and Gratifications Theory (UGT) to investigate the impact of social media, Internet gaming, and online shopping on the PWB of young adults in Malaysia. The study identified gaps in the UGT's ability to explain addictive behaviours and recommended expanding the theory to include concepts of digital addiction. It emphasized the need for tailored interventions and public awareness campaigns to address excessive gaming and called for collaborative efforts between mental health professionals and policymakers to mitigate its negative impact on mental health.